The ability of two chlorine dioxide chemistries to inactivate human papillomavirus‐contaminated endocavitary ultrasound probes and nasendoscopes. Issue 8 (4th February 2020) - Meyers, Craig; Milici, Janice; Robison, Richard
Abstract: Sexual transmission is the most common pathway for the spread of Human papillomavirus (HPV). However, the potential for iatrogenic HPV infections is also real. Even though cleared by the Food and Drug Administration and recommended by the World Federation for Ultrasound in Medicine and Biology, several disinfectants including glutaraldehyde and o ‐phthalaldehyde have shown a lack of efficacy for inactivating HPV. Other methods such as ultraviolet C and concentrated hydrogen peroxide have been shown highly effective at inactivating infectious HPV. In this study, two chlorine dioxide systems are also shown to be highly efficacious at inactivating HPV. An important difference in these present studies is that as opposed to testing in suspension or using a carrier, we dried the infectious virus directly onto endocavitary ultrasound probes and nasendoscopes, therefore, validating a more realistic system to demonstrate disinfectant efficacy. Highlights: Nonsexual transmission of Human Papillomavirus (HPV) is a real potential risk. For the first time, two chlorine dioxide chemistries are tested and shown to be efficacious in killing HPV. This study tested drying the infectious virus directly onto endocavitary ultrasound probes and nasendoscopes, therefore validating a more realistic system to demonstrate disinfectant efficacy.